2022-RA-763-ESGO Contrasting outcomes in two cases ofuterinePEComa. (20th October 2022) - Tiwari, Mansi; Miah, Aisha; Wise, Olga; Sayasneh, Ahmad; Nath, Rahul; Rajkumar, Savithri; Kolomainen, Desiree; Mehra, Gautam
Abstract : Introduction/Background: Uterine PEComa (Perivascular epitheloid cell neoplasm) are rare tumours defined by WHO as a group of mesenchymal tumours composed of histological and immuno-histochemically distinct perivascular epithelioid cells. They are usually detected early and have a good prognosis, rarely they are aggressive with poor prognosis. Currently, there is no established role for adjuvant chemotherapy or immunotherapy. We report two contrasting cases of PEComa with varied prognosis. Methodology: We reviewed the records of two women with uterine PEComa at Guy's & St Thomas' Cancer center in the United Kingdom. Information was recorded on presentation, treatment and outcomes. Results: Two women diagnosed with uterine PEComa. One had an advanced aggressive PEComa with synchronous FIGO Stage-II tubal malignancy. The other had an early stage-Ia uterine PEComa. Both women underwent primary surgical treatment. The early-stage PEComa had a good outcome following surgery and did not have adjuvant therapy. Her disease-free interval is 60 months and continues surveillance. The second woman had FIGO-IIb PEComa with recurrence within 2 months following surgery in vagina and lung. She underwent vaginal and thoracic surgery resecting tumors. She did not receive chemotherapy for ovarian cancer due to medical fitness. PEComa relapsed aggressively in the pelvis, lungs and diaphragm within 6 months and she was treated with Sirolimus and Nab-sirolimus. With this aggressive tumour, her overall survival was 14 months. Conclusion: This illustrates the natural history of a rare uterine tumour (PEComa) and the management in rare presentations with aggressive tumours. The management can be challenging requiring mutidisciplinary approach. There is lack of evidence how to manage recurrence of PEComa not salvaged by surgery.